The AIDS pandemic : impact on science and society - Mayer, Kenneth H.; Pizer, Hank (Elsevier Academic Press, 2005)
The AIDS Pandemic explores the ways in which HIV/AIDS has, and continues to transform the wide range of related disciplines it touches. Novel perspectives are provided by a unique panel of internationally recognised experts who cover the unprecedented impact onf AIDS on culture, demographics and politics around the world, including how it affected the worlds' economy, health sciences, epidemiology and public health. This important far- reaching analysis uses the lessons learned from a wide array of disciplines to help us understand the current status and evolution of the pandemic, as it continues to evolve. * Unique and timely presentation of new theories and perspectives * Concentrates on the changes that have taken place in a broad array of related disciplines * Provides key contextual information, for those new to the field or at interface areas between disciplines * Includes an international focus on evolving African and Asian experiences * Focuses on the current strategies for developing vaccines and microbicides * Outlines harm reduction and prevention programs * Explores issues related to delivery of life-saving AIDS medications in resource-constrained environments.